Relationships between depth and δ15N of Arctic benthos vary among regions and trophic functional groups. (May 2018) - Stasko, Ashley D.; Bluhm, Bodil A.; Reist, James D.; Swanson, Heidi; Power, Michael
Abstract: Stable isotope ratios of nitrogen (δ 15 N) of benthic primary consumers are often significantly related to water depth. This relationship is commonly attributed to preferential uptake of 14 N from sinking particulate organic matter (POM) by microbes, and suggests that relationships between δ 15 N and water depth may be affected by local POM sources and flux dynamics. We examined the relationships between δ 15 N and water depth (20–500 m) for six trophic functional groups using a mixed effects modelling approach, and compared relationships between two contiguous Arctic marine ecosystems with different POM sources and sinking export dynamics: the Canadian Beaufort Sea and Amundsen Gulf. We demonstrate for the first time in the Arctic that δ 15 N values of mobile epifaunal carnivores increased as a function of depth when considered separately from benthopelagic and infaunal carnivores, which contrarily did not exhibit increasing δ 15 N with depth. The δ 15 N of suspension/filter feeders, infaunal deposit feeders and bulk sediment also increased with water depth, and the slopes of the relationships were steeper in the Amundsen Gulf than in the Beaufort Sea. We propose that regional differences in slopes reflect differences in POM sources exported to the benthos. In the Beaufort Sea, terrestrial POM discharged from the Mackenzie River quantitatively dominates the sedimentary organic matter across the continental shelf and slope, dampening change in δ 15 N of benthic POM with depth. In the Amundsen Gulf, we attribute a faster rate of change in δ 15 N of POM with increasing depth to larger contributions of marine-derived POM to the benthic sedimentary pool, which had likely undergone extensive biological transformation in the productive offshore pelagic zone. Differences in POM input regimes among regions should be considered when comparing food webs using stable isotopes, as such differences may impact the rate at which consumer δ 15 N changes with depth. Highlights: Arctic marine suspension and infaunal deposit feeder δ 15 N increased with water depth. Contrary to previous Arctic work, benthic carnivore δ 15 N also increased with depth. Slopes of δ 15 N-depth relationships differed between two contiguous Arctic regions. Regional differences are attributed to organic matter source and flux regimes. Highlights variation in benthic/pelagic trophic pathway use among and within groups.